PEMBELAJARAN BIOLOGI MODEL PROBLEM BASED LEARNING (PBL) DISERTAI DIALOG SOCRATES (DS)TERHADAP HASIL BELAJAR DITINJAU DARI KEMAMPUAN MEMECAHKAN MASALAH KELAS X - Hariatik, Hariatik; Suciati, Suciati; Sugiyarto, Sugiyarto (Universitas Negeri Malang, 2017)
Learning needs to be considered internal factors of students, such as problem-solving ability that are very important for students and their future. The result of the test of the students of grade X IPA 4 SMA Negeri 8 Surakarta on Biology subject matter of environmental pollution, problem solving ability is low. This is limited to the results of learning is still product-oriented, which is limited to the application of conceptual learning with rote. Learning model used in overcoming the problem is model Problem Based Learning accompanied by Dialog Soctares (PBLDS). This study aims to determine the influence and interaction of PBLDS in terms of problem solving to affective, cognitive and psychomotor student’ achievement. Subjects in this study were students of class x SMA Negeri 8 Surakarta. This study was included in a quasi experiment using a post-test control design. The data generated in this study were analyzed using anava test. The research instruments used were observation sheets and multiple choice tests. The results showed that the influence and model model of PBLDS viewed from the results of problem solving ability affective, cognitive and psychomotor learning results. This can be seen from the results of the anova test shows a significance value of less than 0.05.